2015
DOI: 10.1175/jcli-d-13-00646.1
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Analysis of Downscaled and Explicitly Simulated North Atlantic Tropical Cyclone Tracks

Abstract: A realistic representation of the North Atlantic tropical cyclone tracks is crucial as it allows, for example, explaining potential changes in U.S. landfalling systems. Here, the authors present a tentative study that examines the ability of recent climate models to represent North Atlantic tropical cyclone tracks. Tracks from two types of climate models are evaluated: explicit tracks are obtained from tropical cyclones simulated in regional or global climate models with moderate to high horizontal resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 90 publications
6
74
0
Order By: Relevance
“…The U.S. CLIVAR HWG experimental suite provides a common experimental framework to isolate model-dependent responses. Preliminary multimodel results have been reported in Zhao et al (2013), Daloz et al (2015), Shaevitz et al (2014), and Walsh et al (2015).…”
Section: Introductionmentioning
confidence: 87%
“…The U.S. CLIVAR HWG experimental suite provides a common experimental framework to isolate model-dependent responses. Preliminary multimodel results have been reported in Zhao et al (2013), Daloz et al (2015), Shaevitz et al (2014), and Walsh et al (2015).…”
Section: Introductionmentioning
confidence: 87%
“…Figure 7 compares the probability distribution of the intensification rate of major hurricanes near the US coast 2 between the quiescent period and the more active period while column 5 and 6 in Table 6 compares the average intensification rate between the two periods for both hurricanes and major hurricanes. We note that because the period considered here is shorter than in Kossin (2017Kossin ( ) (1980Kossin ( -2010Kossin ( vs 1970Kossin ( -2015, the differences measured in observation are no Table 6 Basin-wide hurricane activity and 6-hourly intensification rate near the US coast between the most recent quiescent and active periods…”
Section: Landfalling Hurricanesmentioning
confidence: 96%
“…These disturbances are then allowed to propagate based on the largescale general circulation of the atmosphere and, finally, the intensity of the storms along each track is computed using a deterministic coupled-atmosphere tropical cyclone model which uses the atmosphere and near-surface ocean thermodynamic conditions. When the technique is applied to current climate conditions, the disturbances which survive and develop into full grown tropical cyclones have been shown to have fairly realistic physical characteristics (Emanuel et al 2008) and direct comparisons with climate model outputs have shown that tropical cyclone activity produced using this downscaling approach generally compares favorably to the cyclone activity explicitly simulated by climate models, in particular over the Atlantic (Daloz et al 2015;Emanuel et al 2010). This downscaling technique has been applied extensively to study a range of problems, including, but not limited to tropical cyclone activity during the Pliocene epoch (Fedorov et al 2010), hurricane-related precipitation risk over Texas (Zhu et al 2013;Emanuel 2017), poleward migration of tropical cyclone activity (Kossin et al 2016), storm surge threat to New York City (Lin et al 2010(Lin et al , 2012Reed et al 2015) as well as other potentially vulnerable locations , medicanes Emanuel 2013, 2017), polar lows (Romero and Emanuel 2017) and, finally, projected change in global hurricane activity (Emanuel 2013), hurricane-related damage (Emanuel 2011;Mendelsohn et al 2012) and tropical cyclone season length (Dwyer et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This study uses 26 The influence of the large scale environment on TC has initally been studied by Strachan et al (2013) and Bell et al (2013Bell et al ( , 2014 for the HadGEM1 model, then by Roberts et al (2015) for the HadGEM3 model. More generally, the HadGEM3 TC simulation skill has been tested in a large GCM intercomparison carried out by the CLIVAR Hurricane Working Group (Shaevitz et al 2014) including the response to natural and forced variability (Walsh et al 2014;Daloz et al 2015). Walters et al (2011) showed the N96 and N216 models have relatively small biases over the Mediterranean in DJF.…”
Section: The Hadgem3 Climate Modelmentioning
confidence: 99%